College geometry : a problem-solving approach with applications. - Musser, Gary L.; Trimpe, Lynn E.; Maurer, Vikki R (Upper Saddle River, N.J. : Pearson Prentice Hall, 2008)
"For courses in Geometry or Geometry for Future Teachers." This popular book has four main goals: 1. to help students become better problem solvers, especially in solving common application problems involving geometry; 2. to help students learn many properties of geometric figures, to verify them using proofs, and to use them to solve applied problems; 3. to expose students to the axiomatic method of synthetic Euclidean geometry at an appropriate level of sophistication; and 4. to provide students with other methods for solving problems in geometry, namely using coordinate geometry and transformation geometry. Beginning with informal experiences, the book gradually moves toward more formal proofs, and includes special topics sections.
Problem Solving, Geometric Shapes, and Measurement Problem Solving in Geometry Geometric Shapes and Measurement Perimeter, Area, and Volume Formal Synthetic Euclidean Geometry Reasoning and Triangle Congruence Parallel Lines and Quadrilaterals Similarity Circles Alternate Approaches to Plane Geometry Coordinate Geometry Transformation Geometry Elementary Logic Inequalities in Algebra and Geometry Non-Euclidean Geometry Table of Contents provided by Publisher. All Rights Reserved.
Includes index.
1
Keywords: Geometry